Pengaruh Corporate Gorvernance terhadap Tax Avoidance dengan Profitabilitas sebagai Pemoderasi - Muhammad Yusuf; Heny Herawati (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2021)
This study aims to prove empirically the effect of corporate governance with indicators Independent Commissioner, Institusional Ownership and Audit Committee on tax avoidance with profitability as Moderating in Mining sector companies listed on the Indonesia Stock Exchange (IDX) during the 2016-2019 period. Samples were taken using a purposive sampling method with certain criteria, during the study period. Based on the criteria set by panel data usage, 64 data can be processed. The analytical method used is panel data regression and moderated regression analysis which is processed using Eviews 10. The result of this study indicated that: (1) independent commissioner has no effect on the occurrence of tax avoidance. (2) institusional ownership has a negative effect on the occurrence of tax avoidance. (3) audit committee has a negative effect on the occurrence of tax avoidance. (4) independent commissioner moderated through profitability does not affect tax avoidance. (5) institusional ownership moderated through profitability influences and strengthens tax avoidance. (6) audit committee moderated through profitability influences and weakens tax avoidance.